2011
DOI: 10.1007/s10658-011-9760-z
|View full text |Cite
|
Sign up to set email alerts
|

Pathogenic Botryosphaeriaceae associated with Mangifera indica in the Kimberley Region of Western Australia

Abstract: Members of the Botryosphaeriaceae, in particular Lasiodiplodia theobromae, Neofusicoccum parvum, Neofusicoccum mangiferae and Botryosphaeria dothidea, commonly cause stem cankers, dieback and stem end rot of mangoes worldwide. In the current study, eight taxa of Botryosphaeriaceae were identified as canker-associated fungi, pathogens, potential pathogens or endophytes of mangoes in the Kimberley, Australia. These include Neoscytalidium novaehollandiae, Neoscytalidium dimidiatum, Pseudofusicoccum adansoniae, P.… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

2
81
0
2

Year Published

2011
2011
2024
2024

Publication Types

Select...
7
1

Relationship

2
6

Authors

Journals

citations
Cited by 109 publications
(91 citation statements)
references
References 44 publications
2
81
0
2
Order By: Relevance
“…(36). Já em inoculações em ramos e frutos de mangueira, esta espécie produziu lesões que foram significativamente diferentes do controle (37). Esta espécie foi primeiramente descrita por Pavlic et al (32), causando morte em ramos de Adansonia gibbosa F. Muell.…”
Section: Resultsunclassified
“…(36). Já em inoculações em ramos e frutos de mangueira, esta espécie produziu lesões que foram significativamente diferentes do controle (37). Esta espécie foi primeiramente descrita por Pavlic et al (32), causando morte em ramos de Adansonia gibbosa F. Muell.…”
Section: Resultsunclassified
“…In this study we found this species from non-native environments on Eucalyptus dunnii in eastern Australia and Corymbia torelliana in north-eastern Australia. Botryosphaeriaceae are generally opportunistic host colonists and have been shown to colonise exotic host species in their endemic habitat (Burgess et al, 2006b;Pérez et al, 2010;Sakalidis et al, 2011). South Africa has large eucalypt plantations and Australia has eucalypts in both natural and non-natural (plantation, ornamental) settings.…”
Section: Discussionmentioning
confidence: 99%
“…They were sequenced as described by Sakalidis et al (2011a). Identity was confirmed by phylogenetic analysis using the program PAUP 4.0b10 (Swofford 2003) as described previously (Sakalidis et al 2011c).…”
Section: Molecular Identificationmentioning
confidence: 99%
“…Many members have a broad host range (Punithalingam 1976(Punithalingam , 1980, they fruit on senescing tissue , are found in above ground plant parts (Johnson et al 1992) and multiple species are found often within localised infections in the host tissue (Sakalidis et al 2011a, b;Spagnolo et al 2011). However; unlike other Class III fungi they have occasionally been observed in host seeds (Johnson et al 1998;Bihon et al 2011) and there is also evidence of infections in horticultural crops occurring via pruning wounds (Brown and Hendrix 1981;Smith et al 1994Smith et al , 1996Amponsah et al 2011;Sakalidis et al 2011c). Pathogenicity trials are successfully used to prove potential for disease development (Amponsah et al 2011;Sakalidis et al 2011c) but little is known about possible passive (endophytic) or delayed active (latent pathogen) life stages that may also initiate from the same infections.…”
Section: Introductionmentioning
confidence: 99%
See 1 more Smart Citation